PERKARA GUGAT CERAI PADA PENGADILAN AGAMA SORONG - F.A Satria Putra (Prodi Akhwal Syahsiyyah IAIN Sorong, 2021)
Every couple wants unity in building a household, but the reality shows that the divorce rate is increasing. Now in some circles of society marriage is no longer considered a sacred social institution so that when a problem or dispute occurs, divorce is immediately an option. This study discusses